Understanding Consumers Engagement and Adoption of Social Media Marketing in Fashion Industry in Saudi Arabia: Insights though the Lens of the Theory of Planned Behavior - Alqutub, Kholoud (British Journal of Marketing Studies, 2024)
This study explores the adoption of social media marketing activities by Fashioned industry, examining context through The Theory of Planned Behavior. As social media continues to dominate as a pivotal marketing arena, understanding consumers’ engagement across various platforms becomes imperative for marketers and researchers alike. This research aimed to ascertain if the Theory of Planned Behavior could effectively elucidate as well as predict consumers’ engagement with social media marketing activities beyond a single platform. Conducting a non-probability convenience sampling method, study involved 656 participants above 18 years old residing in Saudi Arabia. An online survey gathered data, subsequently analyzed through regression analyses. Results revealed that attitude emerged as the most influential factor in predicting behavioral intent to involve with social media marketing activities, tracked closely by subjective norms. Intriguingly, perceived behavioral control did not significantly predict this behavioral intent. Furthermore, the intention to engage demonstrated a strong association with actual engagement. The implications suggest a strategic focus for social media marketers: influencing attitudes and subjective norms to heighten engagement across diverse social media platforms. Additionally, the study indicates a shift towards Theory of Reasoned Action as a more appropriate predictive model for engagement, excluding perceived behavioral control. These insights offer valuable guidance for businesses seeking to optimize their social media, marketing strategies across various platforms within the Fashioned industry.